PEMBENTUKAN PORTOFOLIO OPTIMAL DENGAN MODEL INDEKS TUNGGAL PADA SAHAM IDX BUMN 20 DI BEI - Leki, Rofinus; Fatih, Hardika Muhammad (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2025)
Abstract: At the beginning of 2020, the COVID-19 pandemic caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) hit the world, including Indonesia. The COVID-19 protocol policy implemented to break the chain of virus spread has limited business activity, resulting in a decline in the performance of issuers. However, this situation actually triggered an increase in the number of investors in the capital market, who saw an opportunity to shift investment activities to stock trading as an alternative income. This phenomenon shows that the capital market is increasingly in demand even amidst the uncertainty of the pandemic.  Stock investment involves analysis of the returns and risks associated with financial assets. Rational investors try to choose efficient shares to maximize returns with minimal risk. The Indonesian Stock Exchange (BEI) provides stock indexes to help investors, one of which is IDX BUMN 20, which includes 20 shares of State-Owned Enterprises (BUMN), Regional-Owned Enterprises (BUMD), and their affiliates. BUMN shares are considered safer because they are managed by the state, have high liquidity, and often distribute dividends to shareholders.  This research aims to analyze the optimal portfolio formation of IDX BUMN 20 shares using a single index model during the 2021–2022 period. It is hoped that the results of this research will provide insight for investors in making rational investment decisions and maximizing profits with controlled risks.   Keywords: Investment, Stocks, Capital Markets, Index IDX BUMN 20